Dynamic characterization of wine astringency profiles using modified progressive profiling. (June 2019) - Kang, Wenyu; Niimi, Jun; Muhlack, Richard A.; Smith, Paul A.; Bastian, Susan E.P.
Abstract: Wine astringency is important for quality and consumer acceptance. Perception of this mouthfeel is temporal and can be separated further into unique textural sub-qualities. Quantitative data on these astringent sub-qualities in wine however are poorly understood. The aim of this study was to characterize the dynamic astringency profiles of 13 Australian commercial red wines and 2 rosés made from 11 grape varieties using modified progressive profiling by a trained sensory panel (n = 8). Seven attributes generated and defined by the panel (overall astringent intensity and 6 sub-qualities: pucker, mouth coat, dry, grippy, adhesive and graininess) were scored at six time periods (each lasting 10 s), with 20 s gap between each time period. Attributes were rated on 15 cm scales with anchors at 10 and 90% and samples were evaluated in duplicate. The wine composition as well as phenolic profiles were determined. Intensities of astringent sub-qualities were correlated with overall intensity, but the sub-quality profiles at a specific evaluation period and the progression of an attribute varied differently depending on the wine. The discrimination of wines at each time interval was dependent on attribute, and the relative importance of each astringent sub-quality varied at different evaluation periods. Correlations between mouthfeel attributes and chemical measures were established. This study demonstrated the utilisation of modified progressive profiling for wine astringency evaluation, providing a tool to capture quantitative data on astringent sub-qualities in wine. Graphical abstract: Unlabelled Image Highlights: Modified progressive profiling (PP) was used to characterize wine astringency. Subtle differences in wine astringency quality were distinguished. Chemical composition including phenolic profiles of wine samples were measured. Astringent sub-quality and chemical measure correlations were revealed.